Perilaku Nyamuk Mansonia dan Potensi Reservoar dalam Penularan Filariasis di Desa Gulinggang Kabupaten Balangan Provinsi Kalimantan Selatan - Supriyono Supriyono; Suryani Tan; Upik Kesumawati Hadi (Loka Litbang Kesehatan Pangandaran, 2017)
Mansonia is the one of mosquitoes that can transmit filariasis in Indonesia. The research wasconducted to determine diversity of Mansonia in Gulinggang Village Balangan District South KalimantanProvince and the role of reservoir on transmitting filariasis. The research was conducted in January until Mei2015 with cross sectional data collection. Adult mosquitoes were collected by Bare Leg Collection method onthree houses, which have patients with positive filaria. Adult mosquitoes collecting were done in indoor andoutdoor start from 18.00-06.00. Blood sampling were done on cats that maintenance by the origin people toobserve of microfilaria. The result showed there were five species of Mansonia i.e. Ma. uniformis, Ma. dives,Ma. annulifera, Ma. annulata, and Ma. bonneae. Ma. uniformis was the most collected mosquitoes indoorbiting (37.99%), and Ma. dives was the most outdoor biting (56.80%). The biting activity of Ma. uniformiswas peak indoors at 18:00–18:45 and outdoor at 20:00–20:45. The biting activity of Ma. dives was peakoutdoor at 19:00-19:45. Eight from ten (80%) domestic cats were positive of microfilaria. Based on theresult, it was conclude that filariasis in Gulinggang village was supported by the existence of domestic catand the vectors.